The Effect of Different Thermal Treatments on Corrosion Behavior of the Hydroxyapatite Coated on Ti-6Al-4V Alloy by Electrophoretic Deposition and Dip Coating - Hasan, Aqeel Faleeh; Elttayef, Abdul Husain Khudhair; Khalaf, Mohammed Khammas (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research, the study of thermal treating by laser, plasma glow discharge and tubular furnace on Ti-6Al-4V alloy coated with hydroxyapatite by methods of dip coating and electrophoretic deposition .A group of samples was coated by dip coating and another group was coated by electrophoretic deposition. The first group was treated by pulse laser 10 (mJ) as energy for samples from both coating with uniform distributed pulses on every single sample surface, The second thermal treating was made by plasma glow discharge in a locally made system with argon atmosphere, 600 Volt , and 6 cm distance between the electrodes, The third treating was made by tubular furnace in air atmosphere and 400 °C for 1 hour duration. Then the samples were tested by optical microscope, XRD, SEM, and the corrosion characteristic with open circuit potential (OCP) and polarization curve (Tafel), The results showed that the samples tr eated by tubular furnace were the best where the corrosion rate was reduced to 3.567×10-4 mm/y for the dip coated samples and 7.221×10-4 mm/y for the electrophoretic deposited samples compared with 9.396×10-3mm/y for uncoated sample.